KORELASI ANTARA PENERIMAAN DIRI DAN DEPRESI PADA KOMUNITAS LGBT (Lesbian, Gay, Biseksual dan Transgender) - Pramasari, Putri Adelya (Raheema, 2023)
Background: Self-acceptance is the state of a person who understands his or her own weaknesses and strengths, has accepted all of their own characteristics, and is willing to live with them. Individuals who do not have good self-acceptance will find it difficult to control their emotions and can cause various emotional difficulties such as anger and depression. Depression is a prolonged emotional disorder characterized by sadness, moodiness, feelings of lack of enthusiasm in carrying out daily activities, and feelings of guilt. Depression is often associated with a state of low self-acceptance. Depression is usually experienced by deviant sexual orientation groups such as lesbians, gays, bisexuals, and transgender or transsexuals (LGBT). Aim: This study aims to determine the correlation between self-acceptance and depression in the LGBT community. Method: Observational-analytical research design with a cross-sectional approach and the snowball sampling method with up to 94 members of the LGBT community in one of West Kalimantan District as research subjects. The statistical test used is the Spearman correlation test. Results: There were 94 respondents, consisting of men (95.7%) and women (4.3%), with an age range of 18–52 years. Respondents had the sexual orientations of lesbian (4.3%), gay (42.6%), bisexual (6.4%), and transgender (46.8%). After being tested with Spearman correlation test, the p value = 0,567, which means that there is no correlation between self-acceptance and depression. The correlation coefficient value is 0,060 which indicates the correlation between the two variables is in the same direction because it is positive but there is almost no correlation.